Review article: Primary aeromedical retrievals in Australia: An interrogation and search for context. (14th November 2019) - King, Jemma C; Franklin, Richard C; Robertson, Anita; Aitken, Peter J; Elcock, Mark S; Gibbs, Clinton; Lawton, Luke; Mazur, Stefan M; Edwards, Kristin H; Leggat, Peter A
Abstract: Primary aeromedical retrievals are a direct scene response to patients with a critical injury or illness using a medically equipped aircraft. They are often high‐acuity taskings. In Australia, information on primary retrieval taskings is housed by service providers, of which there are many across the country. This exploratory literature review aims to explore the contemporary peer‐reviewed literature on primary aeromedical retrievals in Australia. The focus is on adult primary aeromedical retrievals undertaken in Australia and clinical tools used in this pre‐hospital setting. Included articles were reviewed for research theme (clinical and equipment, systems and/or outcomes), data coverage and appraisal of the evidence. Of the 37 articles included, majority explored helicopter retrievals ( n = 32), retrieval systems ( n = 21), compared outcomes within a service ( n = 10) and explored retrievals in the state of New South Wales ( n = 19). Major topics of focus included retrieval of trauma patients and airway management. Overall, the publications had a lower strength of evidence because of the preponderance of cross‐sectional and case‐study methodology. This review provides some preliminary but piecemeal insight into primary retrievals in Australia through a localised systems lens. However, there are several areas for research action and service outcome improvements suggested, all of which would be facilitated through the creation of a national pre‐hospital and retrieval registry. The creation of a registry would enable consideration of the frequency and context of retrievals, comparison across services, more sophisticated data interrogation. Most importantly, it can lead to service and pre‐hospital and retrieval system strengthening.